Cross-cultural business behavior : a guide for global management - Gesteland, Richard R. (Copenhagen Business School Press ; Distribution : International Specialized Book Services, 2012)
The theme of this new edition is CHANGE. First of all, cultures change. In markets around the world, business behavior is constantly evolving, impelled by generational shifts, improvements in education, and (especially) increasing exposure to the world marketplace. That is why all of the book's 43 'Negotiator Profiles' have been thoroughly updated, with new cases and fresh examples added. In addition to the change in culture, international managers' challenges have changed too. For example, just a few years ago, participants at global management seminars around the world were mainly interested in how to communicate and negotiate with overseas partners. But, they now find that their toughest challenges are how to manage overseas subsidiaries, strategic alliances, and international partnerships. To reflect these new realities, the book's time-tested framework for understanding cross-cultural negotiating behavior has been expanded to include a wide variety of practical pointers on managing in today's global marketplace. This fifth edition is important for everyone involved with global management, whether student or manager, because cultures and business challenges do change. The book is an essential survival guide for doing business in cultures other than one's own.